2017
DOI: 10.3892/ol.2017.7708
|View full text |Cite
|
Sign up to set email alerts
|

miR‑433 accelerates acquired chemoresistance of gallbladder cancer cells by targeting cyclin M

Abstract: Abstract. Resistance to chemotherapy is associated with dismal prognosis in patients with gallbladder cancer. Cyclin-dependent kinase 10 (CDK10) influences the chemosensitivity of gallbladder cancer cells, and cyclin M is the activating factor and binding partner of CDK10. To determine the effect of CDK10 or cyclin M overexpression on chemosensitivity, gemcitabine-resistant (GR) subclones were established from CDK10 or cyclin M stable transfectants. Stable overexpression of CDK10 increased the sensitivity to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Bioinformatics analysis was then conducted to search for the miRNA targets of LINC00657. The latter contains a complementary binding site for miR-433 (Figure 3(b)), and this miRNA was selected for further investigation because this miRNA frequently participates in the malignancy of many types of human cancer [32][33][34]. After validation of the efficacy of miR-433 mimics transfection (Figure 3(c), P < 0.05), a luciferase reporter assay was performed to test whether LINC00657 can bind to miR-433 in PDAC cells.…”
Section: Linc00657 Serves As a Molecular Sponge For Mir-433 In Pdac Cellsmentioning
confidence: 99%
“…Bioinformatics analysis was then conducted to search for the miRNA targets of LINC00657. The latter contains a complementary binding site for miR-433 (Figure 3(b)), and this miRNA was selected for further investigation because this miRNA frequently participates in the malignancy of many types of human cancer [32][33][34]. After validation of the efficacy of miR-433 mimics transfection (Figure 3(c), P < 0.05), a luciferase reporter assay was performed to test whether LINC00657 can bind to miR-433 in PDAC cells.…”
Section: Linc00657 Serves As a Molecular Sponge For Mir-433 In Pdac Cellsmentioning
confidence: 99%
“…On the one hand, Gotanda and colleagues reported that miR-433 increased sensitivity to 5-FU in HeLa cells by regulating of thymidylate synthase [19]. However, Yu et al and Weiner-Gorzel et al respectively demonstrated that miR-433 could promote resistance to gemcitabine or paclitaxel in gallbladder and ovarian cancer cells [20,21]. On the other hand, Lin and colleagues observed that miR-433 suppressed hematopoietic cell differentiation in myeloproliferative neoplasms [22].…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, overexpression of CDK10 increased chemosensitivity to cisplatin and epirubicin in SMMC-7721 cells but not HepG2 cells ( 31 ). Furthermore, overexpression of CDK10 increased gall bladder cancer sensitivity to gemcitabine ( 69 ). Anticipating a mechanism similar to endocrine therapy resistance in breast cancer, CDK10 expression was shown to downregulate c-Raf levels in BTC ( 64 , 69 ).…”
Section: Cdk10 As a Tumor Suppressor In Gastrointestinal And Hepatobiliary Cancersmentioning
confidence: 99%
“…Furthermore, overexpression of CDK10 increased gall bladder cancer sensitivity to gemcitabine ( 69 ). Anticipating a mechanism similar to endocrine therapy resistance in breast cancer, CDK10 expression was shown to downregulate c-Raf levels in BTC ( 64 , 69 ). Furthermore, in gall bladder cancer, knockdown of c-Raf resulted in a significant increase in gemcitabine sensitivity in cells overexpressing CDK10 ( 69 ).…”
Section: Cdk10 As a Tumor Suppressor In Gastrointestinal And Hepatobiliary Cancersmentioning
confidence: 99%
See 1 more Smart Citation